2020
DOI: 10.15835/nbha48211895
|View full text |Cite
|
Sign up to set email alerts
|

Response of oil flax varieties to abiotic conditions of the Middle Cis-Ural region by formation of seed yield

Abstract: Studying the reaction to the abiotic conditions of the Middle Urals in 16 varieties of oil flax will allow to adapt the culture: increase its productivity and product quality. As a standard, the variety ‘VNIIMK 620’ was sown. The experiments were laid on sod-podzolic medium loamy soil in the grain-grass rotation after winter crops during 2012-2015. During the years of research, the plow layer of the experimental plots had different humus contents - medium and high, mobile phosphorus and exchange potassium - me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It can be concluded that the main factor that significantly affects the performance is the climate since Khajani, Irannezhad, Majidian, & Oraki (2012) observed that almost double of seed yield (2384.28 kg/ha) was recorded on the climate of Iran. Goreeva, Korepanova, Fatykhov, & Islamova (2020) also mentioned that 91.5% of the seed yield in flax cultivation was affected by environment and abiotic factors and 3% from genetic factors.…”
Section: Resultsmentioning
confidence: 99%
“…It can be concluded that the main factor that significantly affects the performance is the climate since Khajani, Irannezhad, Majidian, & Oraki (2012) observed that almost double of seed yield (2384.28 kg/ha) was recorded on the climate of Iran. Goreeva, Korepanova, Fatykhov, & Islamova (2020) also mentioned that 91.5% of the seed yield in flax cultivation was affected by environment and abiotic factors and 3% from genetic factors.…”
Section: Resultsmentioning
confidence: 99%
“…This includes the increasing wear and tear of the farm machinery stock at a lower replacement rate for new machinery, lower incomes, as well as reduced soil fertility due to prolonged irrational use. In such a case, a combination of methods is applied, when a high result is reached at a minimal cost, namely, the tillage at the lowest acceptable level and the use of seeders of combined type [5], [6]. The result was lower costs when arable land productivity was equal for control (standard tillage methods) and experimental plots.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is reported to be one of the oldest crops plants cultivated(Shivaraj et al 2019;Cassuto et al 2022). It is known that ax has the ability to adaptation to extreme conditions and has a culture area(Bourmaud et al 2013;Goreeva et al 2020;Li et al 2022).With respect to the plantation of the cultivar/genotypes considered, 63 out of 80 ax emerged at the trial conditions. Amid the emerged ax cultivar/genotypes, Bison, Mcduff, Hermes, Eckendor , and Mapun genotypes were for the rst time assayed in Turkey.…”
mentioning
confidence: 99%